Development Development of IPAS Student Worksheets Featuring Local Wisdom from South Kalimantan for Fifth-Grade Elementary School Students - Ainun Al Fitria; Yudha Adrian (Journal of Elementary Education, 2026)
Learning activities at SDN Pulau Kerasian currently tend to be teacher-centered and have not fully facilitated the active involvement of students in their learning process. This results in students getting less opportunities to be active such as discussing, one of the main factors causing this lack of integration is the unavailability of media and teaching materials at the school and the teacher's limited time. Therefore, researchers developed teaching materials in the form of LKPD based on local wisdom, the purpose of this study was to describe and determine the level of validity, practicality and attractiveness of LKPD based on local wisdom. The research method used is Research and Development (R&D) with a 4-D development model (Define, Design, Development, Disseminate). Data were collected through validation sheets by experts (media expert lecturers, material expert lecturers, and class teachers as language experts) as well as teacher response questionnaires and 27 students of SDN Pulau Kerasian, then analyzed quantitatively and qualitatively. The results of the study showed that the local wisdom-based science worksheet (LKPD) was declared "Very Valid" with a media validity percentage of 92.67%, material 82%, and language 86.67%. This product was also categorized as "Very Practical" based on a score of 100% from teachers, and "Very Interesting" with an average score of 91.18% from students. It can be concluded that this LKPD is very suitable for use as a learning resource to increase the active involvement and learning motivation of elementary school students.